Beyond Peer Influence: The Combined Effect of Self-Driven Motivation and Strong Family Bonds on Sexual Decision-Making - Irdayani; Widya Apriani; Sri Wahyuni; Nova Ratna Dewi; Hidayana (HM Publisher, 2025)
Introduction: Adolescent engagement in risky sexual behavior remains a significant public health concern. While peer influence is widely studied, understanding the protective roles of intrinsic factors like self-driven motivation and proximal systems such as strong family bonds is crucial for comprehensive intervention strategies. This study aimed to investigate the combined effect of self-driven motivation and family bonds on sexual decision-making among adolescents in Wih Pesam District, Bener Meriah Regency, Indonesia. Methods: A cross-sectional survey was conducted with 198 adolescents. Standardized questionnaires assessed self-driven motivation (including components of needs, drive, and goals), family bonds (overall family support and its dimensions: informational, appraisal, instrumental, emotional), and engagement in risky sexual behavior. Data analysis included descriptive statistics, bivariate chi-square tests, and multivariate logistic regression. Results: Findings indicated that 45.5% of adolescents engaged in risky sexual behavior. A majority reported high overall self-driven motivation (46.5%) and high overall family support (49.5%). Bivariate analyses revealed significant associations between components of self-driven motivation, family support, and risky sexual behavior (all p < 0.05). The multivariate logistic regression analysis demonstrated that, after controlling for other factors, higher overall self-driven motivation (High vs. Low: OR=0.40, 95% CI [0.20–0.78], p=0.007) and higher overall family support (High vs. Low: OR=0.25, 95% CI [0.12–0.51], p<0.001) were significantly associated with reduced odds of engaging in risky sexual behavior. Family support emerged as a particularly strong protective factor. The overall multivariate model was significant (p < 0.001) and explained approximately 38% of the variance (Nagelkerke R-squared = 0.38). Conclusion: Both self-driven motivation and strong family bonds are significant protective factors against risky sexual behavior among adolescents in this Indonesian context, with family support showing a more dominant influence. These findings underscore the importance of interventions aimed at fostering adolescents' internal resilience and strengthening positive family environments to promote healthier sexual decision-making, thereby looking beyond peer influence as the sole determinant.